Адміністративно-правова кваліфікація та кваліфікація адміністративного правопорушення (проступку): поняття, ознаки, передумови - Чишко, К. О.; Chyshko, K. O.; Чишко Катерина Олександрівна (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 3 (70). - С. 150-158, 2015)
Зроблено спробу надати найбільш повні дефініції поняттям «адміністративно-правова кваліфікація» та «кваліфікація адміністративного правопорушення (проступку)», визначити їх співвідношення між собою, а також виділити їх ознаки.

Nowadays there is unresolved issue in the science of administrative law. It concerns the correlation of the terms «administrative and legal qualification» and «qualification of an administrative offense». In practice it is directly reflected on the process and quality of conducting qualification, since neither practical activity is impossible without a theoretical basis. The concept of «administrative and legal qualification» and its features are often identified with the criminal and legal qualification that is generally wrong. In order to provide own definitions of «administrative and legal qualification» and «qualification of an administrative offense» the author of the article has analyzed different definitions of these categories and highlighted their characteristics and preconditions. It is noted that the precondition for administrative and legal qualification is unlawful act or omission, which later on must be qualified as an administrative offense, and while qualification of administrative offense the preconditions are committed act (actual precondition) and the presence of administrative and tort norm providing liability for committed infringement. Based on the conducted analysis it is concluded that the correlation of administrative and legal qualification and of administrative offense’s qualification as a whole and a part. This gave reason to consider the concept of «administrative and legal qualification» in the broad and narrow meanings and the content of the latter meaning would be the same as the value of the term «qualification of an administrative offense».

Сделана попытка дать наиболее полные дефиниции понятиям «административно-правовая квалификация» и «квалификация административного правонарушения (проступка)», определить их соотношение между собой и выделить их признаки.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; адміністративно-правова кваліфікація; кваліфікація адміністративного правопорушення; кваліфікація адміністративного проступку; кваліфікація адміністративного делікту; administrative and legal qualification; administrative offense’s qualification; administrative offense’s misdemeanor; administrative offense’s tort; preconditions; административно-правовая квалификация; квалификация административного правонарушения; квалификация административного проступка; квалификация административного деликта